Prevalence, risk factors, and healthcare‐seeking among subjects with esophageal symptoms: A community‐based study in a rural Bangladeshi population. Issue 6 (22nd September 2020) - Rahman, M. Masudur; Ghoshal, Uday C; Kibria, Md. Golam; Sultana, Nigar; Ahmed, Faruque; Rowshon, AHM; Hasan, Mahmud
Abstract: Background and Aim: As there is a scarcity of data on overall prevalence, risk factors, and health‐care utilization of esophageal symptoms using the Rome criteria in the rural population in Asia, we undertook a study with the aims to evaluate: (i) the prevalence of heartburn, chest pain, globus, and dysphagia of presumed esophageal origin; (ii) the prevalence of functional esophageal disorders by Rome III criteria; (iii) the risk factors for esophageal symptoms; and (iv) the health‐care utilization. Methods: This door‐to‐door survey was conducted in three villages (Charcharia, Churain of Dhaka district, and Kharrah of Munshiganj district of Bangladesh) among the adult population (≥18 years) using the translated and validated Enhanced Asian Rome III questionnaire. Results: Of 3559 individuals, 3351 (94.15%) responded (mean age 40.41 ± 16.04 years, female, 1924 [57.4%]). Heartburn was the most common symptom, 863 (25.8%), followed by chest pain, 367 (11%); globus, 285 (8.5%); and dysphagia, 146 (4.4%). At least one symptom was present in 1108 (33.1%) respondents. Based on Rome III criteria, 428 (12.8%), 41 (1.2%), 49 (1.5%), 26 (0.8%), and 524 (15.6%) had heartburn, chest pain, globus, dysphagia, and at least one functional esophageal disorder, respectively. Female gender, lower family income, presence of functional dyspepsia‐irritable bowel syndrome (FD‐IBS) overlap, FD only, and psychological distress were found to be risk factors for esophageal symptoms on multivariate analysis. Among the subjects with any esophageal disorders, 156 (14.1%) consulted any health‐care provider, and 517 (46.6%) took antisecretory medications. Conclusion: Esophageal symptoms are common in the rural community of Bangladesh and are associated with substantial health resource utilization. Abstract : This door‐to‐door survey was conducted in a rural community of Bangladesh among the adult population using the translation‐validated Enhanced Asian Rome III questionnaire with the aims to study: (i) the prevalence of heartburn, chest pain, globus, and dysphagia of presumed esophageal origin; (ii) the prevalence of functional esophageal disorders by Rome III criteria; (iii) the risk factors for esophageal symptoms; and (iv) health‐care utilization. This study suggests that esophageal symptoms are common in the rural community of Bangladesh and are associated with substantial health resource utilization.